PENGARUH PERTUMBUHAN EKONOMI, KETERSEDIAAN TENAGA KERJA, INFRASTRUKTUR DAN KEPADATAN PENDUDUK TERHADAP PENANAMAN MODAL ASING DI KABUPATEN KENDAL - Muhammad Aulia Zul Thirafi (Economics Development Analysis Journal, 2013)
This research aims to analyze the effect of economic growth, availability of labor, infrastructure and population density to foreign direct investment (FDI) in the Kendal Regency either simultaneously or partial. Data analysis method used in this research is the Error Correction Model (ECM). Based on the results of the analysis of ECM in the short term that variables economic growth and infrastructure effect is significant to FDI. In the long term, variables economic growth significantly to FDI in Kendal Regency